Cardiovascular Implications of Preeclampsia. Issue 1 (January 2016) - Burgess, Adriane; Founds, Sandra
Abstract : Abstract: Cardiovascular disease (CVD) is the leading cause of death of women in the United States. Many healthcare providers are unaware of sex-specific factors that affect the development of CVD. Nursing care for women with a history of preeclampsia and their children is presented. Preeclampsia affects 4% to 8% of all pregnancies. Rates have increased by 25% over the past 2 decades. Research supports the link between preeclampsia and risk of future CVD in women and the children of affected pregnancies. Appropriate preconception, prenatal and postpartum education, and surveillance are necessary to improve the long-term health of both mother and infant. Currently, there are no evidence-based interventions specific to the prevention of CVD for women and their children who have been affected by preeclampsia. However, women who have had preeclampsia may require yearly risk factor assessment and education regarding cardiovascular prevention strategies such as smoking cessation, increased physical activity, importance of a healthy diet, and maintenance of a healthy weight. Preeclampsia should be acknowledged by healthcare providers as a CVD risk factor. Appropriate monitoring, education, and CVD preventive strategies need to be implemented with this population and their children. Abstract : Women who develop preeclampsia during pregnancy are at risk for cardiovascular disease later in life.